Munggu Badung Beach Development Strategy as a Child-Friendly Tourist Attraction: Strategi Pengembangan Pantai Munggu Badung Sebagai Obyek Wisata Ramah Anak - Mekarini, Ni Wayan; Arini, Ni Nyoman; Kartimin, I Wayan; Suryaningsih, Ida Ayu Anggreni; Lubis, Richard Marco (Jurnal Ilmiah Hospitality Management, 2023)
study explores the development strategy for transforming Munggu Beach in Badung Regency into a child-friendly tourism destination, a unique approach given that most beaches are not designed with children in mind. Data was collected through in-depth interviews with the management and local stakeholders, as well as direct observation. The findings were then analyzed descriptively. The research identifies four key strategies for developing the beach as an appealing destination for families. First, Munggu Beach should not be a typical beach but should be specifically designed to accommodate children's needs, which would enhance its attractiveness and profitability. Second, due to its location facing the Indian Ocean, the beach's large waves could be leveraged for child-friendly surfing experiences, with appropriate equipment rentals provided. Third, while the coral on the beach can be a safety hazard, coral exploration packages could be developed that cater to children, offering educational and interactive experiences while fostering a love for the sea and its biodiversity. Lastly, the research highlights the need for a prominent sign at the entrance to the beach, coupled with a strong social media presence for promotion. The novelty of this study lies in its focus on adapting a natural coastal environment for child tourism, a segment often neglected in beach development strategies. The urgency of this research is underscored by the growing demand for family-oriented destinations. This study contributes to the field by providing actionable recommendations for creating a child-friendly tourism hub at Munggu Beach, which can attract more visitors, increase profitability, and promote sustainable tourism practices.